Diferencias morfométricas, físicas y organolépticas de dos especies de peces de la familia (Cichlidae) vieja azul (Aequidens rivulatus) vieja colorada (Cichlasoma festae) capturadas en el rio. - Romero Yupa, Mónica Catalina (2018)
This study determined the characteristics of small fish of commercial interest in the coasts of the province of Los Ríos. Samples were collected during several weeks that corresponded from February 2018 to May 2018 at the usual fishing spots of the different artisanal fishermen. The samples were identified at the species level. The old ones were put on ice in a 2: 1 ratio to avoid their decomposition; later they were taken to the bromatology laboratory of the livestock science faculty to perform the appropriate morphometric measurements; subsequently they were cleaned, bleached, dried and stored. A total of 100 fish were acquired, all extracted from fresh specimens, belonging to dos species distributed in dos families. Morphological characteristics of the old ones that differentiate each species were described, and homogeneity of their shape was determined by family. Height data were obtained in three head sites, in the first spine and in the first anal spine, in the same way, their width in the same sites, besides the catalations of these two species were carried out to evaluate their organoleptic characteristics of the meat. By means of an inferential statistic and using a T of Studen it was determined that there are differences of some variables the parameters of the old ones were taken from the left side, finding significance for the species studied in some parameters.